(untitled) (Journal of Health Sciences, 2023)
Introduction: Statins are lipid lowering medications, used for the prevention of cardiovascular diseases (CVD), but have shown to increase the risk of Type 2 diabetes mellitus. The aim of this study was to investigate the effects of high-potency statins, atorvastatin, and rosuvastatin on fasting glucose (FG) and hemoglobin A1c (HbA1c) in CVD patients. Methods: The case–control study included 123 patients from Tuzla Canton, Bosnia, and Herzegovina, with a diagnosis of CVD, treated in three health centers: Public Health Center Gračanica, Banovići, and Čelić. Of total patients, 84 were statin users (39 atorvastatin users and 45 rosuvastatin users) and 39 were not. Demographic data, diagnosis, and data of the therapy were taken from the medical records, as well as data of the FG and HbA1c, measured before or within 3 months of the statin therapy introduction. For the same patients, FG and HbA1c were also measured at least 3 months after the introduction of therapy. Results: Obtained results have shown a significant increase of FG in CVD patients on statin therapy in relation to control (p = 0.034). Comparing the diabetogenic effects of atrovastatin and rosuvastatin, it was found that the HbA1c in patients on atorvastatin therapy was significantly higher comparing to those on rosuvastatain therapy (p = 0.028). The FG was significantly increased (p = 0.027) after atrovastatin therapy. Similar results were obtained in diabetogenic CVD patients, where HbA1c on atorvastatin therapy was significantly higher comparing to HbA1c in those on rosuvastatain therapy (p = 0.039). A significant correlation was found between the increase in FG and HbA1c with the duration of atorvastatin therapy (p = 0.001 and p = 0.033), and between the increase in HbA1c and the duration of rosuvastatin therapy (p = 0.001). Conclusion: Long-term therapy with high-potency statins, atorvastatin, and rosuvastatin, may increase levels of FG and HbA1c in patients with CVD, where atorvastatin shows more significant effects.